ESTIMASI SEBARAN AIR LINDI BAWAH PERMUKAAN BERDASARKAN DATA ELEKTROMAGNETIK PADA AREA TEMPAT PEMBUANGAN AKHIR (TPA) NOINBILA KABUPATEN TIMOR TENGAH SELATAN - Hadi Imam Sutaji; Hery Leo Sianturi; Ali Warsito (Universitas Nusa Cendana, 2023)
This research study is the determination of estimated distribution of subsurface leachate based on electromagnetic data in the Noinbila Final Disposal Site (TPA) area and its surroundings in South Central East Regency. The data used in the form of conductivity and susceptibility values ​​of the measurement results of the GF instrument CMD-4 at coordinate points at certain elevations. The data is processed and displayed in 2D and 3D contour maps with the help of several related software. The results of the analysis provide information that the Noinbila landfill area and its surroundings which are divided into areas A, B, C, D, E and F are not all polluted by leachate below the surface, but only areas D and F are suspected to be polluted. The potential for contamination of areas A, B, C and E below the surface is still possible because these areas have subsurface geology in the form of coral limestone. The potential for this pollution, apart from below the surface, is also possible on the surface because areas A, B, C and E have a lower elevation dominance than areas D and F. For this reason, this potential must be avoided by optimally handling and managing waste. If the handling and management of the waste is related to the efforts of the Noinbila TPA management, then it has been done even though it is still not optimal. The form of handling efforts as a form of waste management is in the form of matters related to the maintenance and repair of the TPA and its facilities and infrastructure, handling of waste before and after at the TPA and leachate water flow through pipelines to the holding pond, stabilization pond and leachate treatment pond.